CALCULATION ANALYSIS OF HEAT CONDUCTIVITY AND AVERAGE HEAT RATE IN CARBON COMPOSITES - Bernardus Crisanto Putra Mbulu; Nereus Tugur Redationo; Febri Valen Herwinsha (Universitas Katolik Widya Karya Malang, 2023)
Carbon is the material most often used in the manufacture of composite materials. Carbon has a fairly high heat conductivity when it is in the form of graphite of 119-165 W.K/m. However, carbon is difficult to form, so another material that has formability is needed. This study used a mixture of carbon, ceramic and wood glue (PVAc) with variations in the main composition of 65% carbon for specimens 1,2,3 and 65% ceramic for specimens 4,5,6. Testing of all specimens was carried out by heating for 30 minutes, followed by temperature data collection every minute. The data that has been obtained is then calculated to determine the value of heat conductivity and average heat rate of each specimen. The highest value of heat conductivity and average heat rate was produced by specimen 2 with a composition of 65% carbon, 15% ceramic and 20% PVAc, where the value for heat conductivity was 95.346 W.K/m and for a heat rate of 206.7 Watt/second. Carbon can increase the conductivity value and heat rate, but if it is mixed with other materials it will certainly be affected, where ceramic affects the surface of the specimen which can cause cracks and reduces the value of the specimen's thermal resistance, while PVAc affects the reduction of surface cracks due to ceramic hardness when heated but can also become insulator in the specimen when bonded to the ceramic